Hull design and stability analysis of rigid tube rib / Muhammad Farhan Haikal Jamaludin - Jamaludin, Muhammad Farhan Haikal (2022)
A rigid-hulled inflatable boat or, in a simpler way, a rigid inflatable boat (RIB), represents a very popular segment of light crafts, offering high performance and additional practical advantages (Pike, 2013). With improvements in the marine sector, large-scale vessels are now replacing many traditional leisure boats on the market. RIBs are high-performance, lightweight boats that combine tube-based vessels with traditional structural vessels. Rubber, sails, and other inflatable materials surround the boat's hull, which is built of either composite material like fibreglass or aluminium.